The effect of neuropeptides on growth and function of bovine articular chondrocytes - Herzog, Amanda (My University, 2007)
Cartilage injury is a central issue in orthopedics to which there is no known physiological treatment. Neuropeptides playa role in the proliferative and reparative processes of many tissue types, but little is known about their effects on articular cartilage. The purpose ofthis study was to investigate the effects ofthe neuropeptides calcitonin gene-related peptide (CGRP), substance P (SP), neuropeptide Y (NPY), and vasoactive intestinal peptide (VIP) on the growth and metabolism of bovine chondrocytes cultivated in monolayer culture. Proliferation and DMMB assays were conducted over an eight day period. Insulin-like growth factor-l was utilized as a positive control to validate the monolayer model. While CGRP showed little effect and NPY showed an inhibitive effect on proliferation, VIP demonstrated some ability to positively augment cartilage (n=8). Finally, SP showed the greatest reparative potential due to the significant increase in both proliferation and glycosaminoglycan production after SP 5 ug/ml. treatment.
The effect of neuropeptides on the growth and function of bovine articular chondrocytes
25 p.
Keywords: Biochemistry; Orthopedics and Rehabilitation